The Relationship Between Family Support and Patient Anxiety Levels in the Emergency Department (ER) - Nabila Lintang Dikmazari (Jurnal Skala Kesehatan, 2026)
Anxiety is common among Emergency Room (ER) patients due to urgent conditions, a stressful setting, and uncertainty about care. Family presence can offer emotional reassurance, information, and a sense of security. This study aimed to examine the relationship between family support and anxiety levels in ER patients. A quantitative cross-sectional design was used with a sample of 93 patients, determined via G Power (power = 0.85, effect size = 0.3). Data were collected using a family support questionnaire and the State-Trait Anxiety Inventory-State (STAI-S) scale. Most respondents were over 50 years old, female, and classified as green triage. The majority reported high family support (89.2%), while 47.3% had low anxiety levels. Spearman’s correlation test revealed a statistically significant negative relationship between family support and anxiety (r = –0.310; p = 0.002), indicating that higher family support is associated with lower anxiety. These findings highlight the family’s critical role as a protective factor in maintaining patients’ psychological stability during emergency treatment. The results support integrating family-centered care into ER protocols and provide a foundation for developing family-based psychosocial interventions in the Emergency Department to reduce patient anxiety and improve overall care experience.